Dragon Ball Z. Vol. 25 - Toriyama, Akira, 1955- (Shonen Jump graphic novel., 2006)
"Shorn of his last vestiges of goodness, the djinn Boo is now pure, undiluted evil! With a single wave of his hand he kills six billion people, leaving only the heroes in Kami-sama's sky palace alive. but for how long?-- P. 4 of cover.